PENGARUH PRODUK, PROMOSI, DAN KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI INTERVENING DI BNI SYARIAH YOGYAKARTA - Y. Djoko Suseno, Okky Setia Arde Prabayu, Erni Widajanti & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
This research is a survey research based on the decline in the number of customers in PT BNI Syariah Branch Yogyakarta from 2013 - 2017. This study aims to examine the significant influence between: product, promotion, service quality and customer satisfaction on customer loyalty at PT Sharia Branch of Yogyakarta. The research population is 380 customers, the sample used is 44% of the population, namely 167. This study uses path analysis with multiple linear regression, using the classic assumption test, t test, F test and coefficient of determination (R2). The results of the t test, namely product, promotion, service quality and customer satisfaction have a significant effect on customer loyalty in PT BNI Syariah Yogyakarta Branch. The results of the coefficient of determination (R2) obtained Adjusted R square (R2) of 0.604 means that the contribution or influence of the product, promotion, service quality and customer satisfaction is 60.4% while the remaining 39.6% is explained by other variables outside this research. Keywords: Loyalty, Products, Promotion, Service quality